2007
DOI: 10.1117/12.713892
|View full text |Cite
|
Sign up to set email alerts
|

PAG segregation during exposure affecting innate material roughness

Abstract: We have developed an improved AFM-based technique to measure intrinsic material roughness (IMR) after base development. We have investigated the contribution of different polymeric PAGs to IMR. These polymeric PAGs include copolymers of several styrenic PAGs with hydroxystyrene. The IMR of these polymer-bound PAGs is reduced relative to that of their nonpolymeric counterparts with DUV exposure. Theses results represent further evidence for PAG segregation during the bake steps as being responsible for increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…15 Some work called into question the exclusive dependence on shot noise as both a limiter and significant determinant of LWR. It was found that no simple relationship exists between IMR and sensitivity and instead some other, more complex relationship between the material properties of the polymer and resist process that is determining both the IMR and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…15 Some work called into question the exclusive dependence on shot noise as both a limiter and significant determinant of LWR. It was found that no simple relationship exists between IMR and sensitivity and instead some other, more complex relationship between the material properties of the polymer and resist process that is determining both the IMR and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several recent studies that have investigated the effects of PAGs that segregate to the top of a resist film 16,17,18 . Again as a means of validating the mesoscale model, a PAG concentration profile in which the PAG segregates to the top of the film was programmed into the simulator.…”
Section: Pag Segregation Impact On Resist Profilementioning
confidence: 99%
“…The surface energy affects at the substrate-resist and resist-air interfaces can induce PAG segregation that will be attracted to or away from interfaces. The segregation of PAG can lead to non-homogenous optical absorption, photo-speed and acid diffusion effects throughout the film 17 . Furthermore, the intermixing of resist and organic BARC species can also reduce the amount of PAG or acid that is available at the bottom of the resist film.…”
Section: Line Width Roughness (Lwr)mentioning
confidence: 99%